For each and everyone : catering for individual differences through learning studies - Lo, Mun Ling; Pong, Wing Yan; Chik, Pui Man Pakey (Book collections on Project MUSE., 2005)
This book describes a three-year research project which built on students' learning experience, and addresses the issue of individual differences in mainstream primary schools in Hong Kong. The Learning Study model described in this volume presents a view of learning which stems from a humanistic interest, and stresses on the possible ""experiences"" that the student has gone through in their learning process.